GENDER DALAM KOMUNIKASI POLITIK AKTIVIS PARTAI ISLAM (Analisis Terhadap Aktivis PBB, PPP dan PKS di Padang) - Alqanitah Pohan (Universitas Islam Negeri Imam Bonjol Padang, 2012)
Affirmative action in gender mainstreaming at politic party, is marked with the existence of quota 30% women role in nomination quota of legislative member inviting pro and contra. There are two perspectives in looking at this gender. First, positivistic perspective (or objective) which sees that women have to be given opportunity in political space, its importance if women to have make of policy. Proper women isn’t it well-balance position with men in legislative because amount residents of more women compared to men. Second the naturalistic perspective (or subjective). Which my tries to express that women have their own responsible and their readiness of women to enter political world. The activities of model political communications of Islamic activist party, activist humanity and with candidate elector of legislative general election 2004 there are three models which conventional model, contemporary model and mutant model.Keywords : Gender, Islamic Activist Party and Political Communications ModelCopyright © 2012 by Kafa`ah All right reservedDOI : 10.15548/jk.v2i1.37